Welfare states in the marketplace: exploring the link between sovereign debt and welfare rights in Europe - Scali, Emma Luce (2018)
This thesis addresses the complicated relationship between sovereign debt and the realisation of economic and social rights (ESR) and applicable international human rights law (IHRL). The central research questions to be addressed by this work include the following: How can sovereign debt threaten the realisation of ESR? What guidance does IHRL provide in relation to the sovereign debt issue? Why have human rights and IHRL been so irrelevant in the design and implementation of responses to the Eurozone sovereign debt crisis, as the Greek case has dramatically revealed? This thesis advances two main arguments. Firstly, the ‘marketisation’ of sovereign financing can be problematic for the realisation of ESR for reasons that go beyond the negative social impacts of austerity or other fiscal consolidation measures. Secondly, this thesis will argue that IHRL has been ineffective in preventing or mitigating the negative ESR impacts of responses to the crisis, not only because of the normative shortcomings of the existing legal framework, but also, and more fundamentally, because of the hegemony of neoliberal morality and its influence upon international law. The ascendancy of neoliberal assumptions, also in legal and human rights reasoning—which, as I will argue, appears to have been confirmed and reinforced rather than reversed, by some of the legal developments that have occurred since the crisis—limits the possibility of international law to constitute an instrument for the affirmation and protection of ESR. This thesis has two main theoretical objectives. Firstly, to provide a more holistic picture of the relationship between sovereign debt (and sovereign financing more generally) and ESR, that is not limited to the ESR impacts of austerity. Secondly, to review and critically analyse the existing international law on ESR—particularly relating to the use of State resources—and on sovereign debt and ESR, in order to assess its current status and post-crisis developments, explore the possible reasons of its irrelevance in the context of the Eurozone debt crisis, and speculate on its future directions.